Nutritional qualities assessment of locally processed spaghetti - Tukura, Bitrus; Daniel Gbubele, Joseph; Mamman, Swaiba (International Journal of Scientific World, 2016)
The quest for cheap and quality food is on the increase, especially during economy crises. Some nutritional properties of the raw and cooked local and industrial spaghetti were determined using standard methods. Concentrations of mineral elements were determined using atomic absorption spectrophotometer. Total ash (0.98±007 %), crude protein (14.28±0.15 %) and carbohydrate (77.95±0.11 %) levels in the raw industrial spaghetti were higher compared to the locally processed raw spaghetti. Carbohydrate and moisture levels for both processed spaghetti increased on cooking, while total ash and protein contents decreased. Crude fiber (0.009±0.00 %), carbohydrate (77.52±0.21 %) and moisture levels in the cooked local spaghetti were higher than in the cooked industrial spaghetti. Proximate contents of the local and industrial raw spaghetti were significantly (P ≤ 0.05) different. Concentrations of mineral elements in the raw locally processed spaghetti were lower than in the industrial spaghetti. Low levels of functional properties were recorded in the local spaghetti. Cooking decreased zinc content in the spaghetti, but significantly (P ≤ 0.05) increased the moisture content, crude fiber, carbohydrate and mineral contents. The spaghetti processed locally may serve as an alternative to the industrial spaghetti.